Effect of Angular Velocity on Sensors Based on Morphology Dependent Resonances - Ali, Amir R. (MDPI, 2014)
We carried out an analysis to investigate the morphology dependent optical resonances shift (MDR) of a rotating spherical resonator. The spinning resonator experiences an elastic deformation due to the centrifugal force acting on it, leading to a shift in its MDR. Experiments are also carried out to demonstrate the MDR shifts of a spinning polydimethylsiloxane (PDMS) microsphere. The experimental results agree well with the analytical prediction. These studies demonstrated that spinning sensor based on MDR may experience sufficient shift in the optical resonances, therefore interfering with its desirable operational sensor design. Also the results show that angular velocity sensors could be designed using this principle.